1974
DOI: 10.1577/1548-8659(1974)103<375:saaepi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Androgen and Estrogen Patterns in the Goldfish, Carassius auratus

Abstract: Monthly plasma androgen levels of male and female adult goldfish (Carassius auratus), determined by competitive protein binding assay, followed patterns corresponding to seasonal environmental fluctuations. Highest androgen levels (ca 33 ng/ml) occurred during the spawning season, and lowest concentrations (ca 9 ng/ml) were found in winter. Monthly plasma estrogen patterns, determined by radioimmunoassay, remained stable for the year at approximately 1.5 ng/ml in the male. Estrogen levels in the female paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 4 publications
2
12
0
Order By: Relevance
“…Fish were intraperitoneally injected with 100 μL of the T injection solution, which resulted in a final T dosage of 3 μg/fish. Previous studies have shown that this dose leads to elevated T concentrations within the physiological range 30–45 min after injection (Huggard et al, 1996; Schreck and Hopwood, 1974). Similarly, a 30 mg/mL solution of estradiol (E 2 ; Sigma) was dissolved in methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Fish were intraperitoneally injected with 100 μL of the T injection solution, which resulted in a final T dosage of 3 μg/fish. Previous studies have shown that this dose leads to elevated T concentrations within the physiological range 30–45 min after injection (Huggard et al, 1996; Schreck and Hopwood, 1974). Similarly, a 30 mg/mL solution of estradiol (E 2 ; Sigma) was dissolved in methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Hormone changes during these reproductive cycles in goldfish have been well characterized (Schreck and Hopwood 1974;Stacey et al 1979;Kagawa et al 1983a;Kobayashi et al 1985Kobayashi et al , 1986Kobayashi et al , 1987bKobayashi et al , 1988. Ovulation in goldfish can be manipulated by changes in water temperature and photoperiod.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of seasonal changes in serum gonadal steroid hormone levels have revealed the seasonal patterns of hormone levels in several species including goldfish (Schreck et al 1974), flounder (Campbell et al 1976), plaice (Wingfield and Grimm 1977), bluefish, mackerel (MacGregor et al 198 1 ) , goby (Bonnin 1979), and several salmonid species (Sanchez-Rodrigues et al Campbell et al 1980;Stuart-Kregor et al 198 1 ;Fostier et al 1982;Scott, Bye, and Baynes 1980;Scott, Bye, Baynes et al 1980;Scott et al 1983). To our knowledge, no such studies have been made in an ictalurid species despite the importance of these species in North American aquaculture (Love11 1979;Bardach et al 1972).…”
Section: Introductionmentioning
confidence: 99%